Effects of commercial kelp extract and plant growth regulators on growth of Gracilaria gracilis in culture - Leitao, Daniela (Department of Biological Sciences, 2014)
The addition of a local commercial seaweed extract (Kelpak®) to crop plants has proven to be beneficial as it improves growth and yields. Its efficiency has been attributed to its production method that involves a cold process, resulting in a product containing significant amounts of plant growth regulators (auxins and cytokinins). The aim of this study was therefore to investigate the effects of this commercial seaweed concentrate (Kelpak®) on the growth of Gracilaria gracilis (Stackhouse) Steentoft, Irvine et Farnham, with a view to the potential in mariculture, especially as this red seaweed is currently under cultivation in South Africa as feed in abalone aquaculture.